Effect of Milling Time and Addition of Graphite on the Morphological Structure of Tin Phosphate Powder Using the Graphine Oxide Template Method for Electrolyte Applications - Nandito, Joseph Bona; Arnoldus, Calvin Santo; Alfarizi, Bachtiar Zuhdi; Prakoso, Bismo Aditiya; Trenggono, Adhitya (International Journal Labs, 2023)
Tin phosphate can be used for electrolyte applications. The solid electrolyte industry has experienced significant growth in recent years. In 2020, the market size of the solid electrolyte industry was estimated at 17.8 million and is expected to reach 56.6 million by 2030 at a CAGR of 12.1% from 2021 to 2030. The growth of the solid electrolyte industry is driven by the increasing demand for batteries. Solid-state batteries are becoming a promising alternative to conventional lithium-ion batteries. This research produces tin phosphate nanoparticles through the synthesis of tin phosphate/GO with a modification of the Hummers reaction, using the GO template method which is used to control the morphology and crystal structure of the synthesized material, and calcined to remove GO and produce tin phosphate powder. The research results show that graphite milling time influences the size of the tin phosphate powder produced, and the size of the Graphene Oxide (GO) template also influences the size of the tin phosphate powder. Grinding time also affects the weight of the powder before and after calcination, as well as the amount of GO and tin phosphate produced. The graphite addition ratio also had a significant effect on the weight of the tin phosphate/GO samples before and after calcination. The ratio of adding 2 grams of graphite to 1 gram of tin produces an optimal weight of tin phosphate after calcination, indicating the effectiveness of using GO as a tin growth template. In addition, XRD analysis showed the identification of three dominant compound phases in the resulting powder, namely potassium ditin (IV) tris(phosphate(V)) (KO12P3Sn2), tin phosphate (SnP2O7), and potassium ferrate (FeKO2).